Identifikasi Pemborosan di Unit Penyaring Minyak Inti Sawit PT. SSS - Sundari, Susanti; Gempito, Alip; Suwarni, Putri Indah (Universitas Teuku Umar, 2021)
On the part of the oil filtering process is the most important stage in the processing of palm kernel at PT. SSS. This is because all production processes are focused on the stages of the process, where the filtered clean oil is directly flowed into the clean oil reservoir until it is ready to be exported to companies that cooperate with PT. SSS. From initial observations, it is known that there is a use of longer time than it should be where the total time for all activities in the oil filtration unit that exceeds the company's standard time is 83.2 minutes and then there are several waiting activities. On the basis of this, this research aims to find out in more detail what wastes are contained in the oil filtering unit and their causes.. This is the first step for continuous improvement for the company. This research method is a descriptive research using Process Activity Mapping (PAM) as a tool to find out all the activities that take place during the stages of the oil filtering process, then classify these activities based on the type of waste. Furthermore, a causal diagram (fishbone diagram) is made to analyze the causes of waste. From the results of the study identified three types of waste, namely over process (73.1%), waiting (20.1%) and motion (6.8%), with the dominant factor of humans being undisciplined in their work as the cause.